Offshoring and Relative Labor Demand in Swedish Firms - Linda Andersson; Patrik Karpaty (Örebro University School of Business, 2007)
The objective of this paper is to analyze relative employment effects in Sweden due to offshoring. In contrast to most previous studies in this field, our analysis is based on firm level data. More specifically the dataset contains Swedish manufacturing firms, 1997-2002. In addition we have access to actual firm level import data on intermediate goods and services, respectively. The results show that the relative demand for high skilled labor is positively affected by service offshoring and offshoring of goods to Asia, but negatively affected by offshoring to high income countries. The relative demand for medium skilled labor is negatively affected by offshoring of goods to Eastern Europe, but positively affected by offshoring to high income countries. In contrast to expectations, the results show that the relative demand for low skilled labor is positively affected by offshoring of goods to Eastern Europe. However, these results are related to very small elasticities, which in turn translates into a small number of jobs affected.
Keywords: F14; F23; L23; 330; Offchoring; firm level; data relative employment; translog cost function